The lion-tamer's daughter and other stories - Dickinson, Peter (Delacorte, 1997)
Each of these stories touches on the idea of a twin, ghostly double of a live person, or a secret self.
The spring -- Touch and go -- Checkers -- The lion-tamer's daughter.
Each of these stories touches on the idea of a twin, ghostly double of a live person, or a secret self.
Keywords: Children's stories, English. / http://id.loc.gov/authorities/subjects/sh85023798; Paranormal fiction / Juvenile fiction.